Integration of Islamic Study in English Language Teaching (ELT) Based on Study Program at the University of Kh. Mukhtar Syafaat Blokagung Banyuwangi - Ridwan, Ridwan; Ilmi, Rizqi Maulana; Fauzi, Nur Imam (Riviera Publishing, 2024)
English is an agreed language as a world/international language, so this course is a course or lesson that must be taken by all students and college students in Indonesia from elementary level to college as a compulsory course in the English Language Teaching (ELT) course series. UIMSYA Blokagung Banyuwangi is a pesantren-based higher education campus, so the purpose of this study is to find out the extent to which educators integrate ELT with Islamic / pesantren studies in accordance with their study program. This study aims to determine the extent to which educators integrate English language learning (ELT) with Islamic studies in accordance with their study program at the KH. Mukhtar Syafaat Islamic Boarding School Blokagung Banyuwangi. The research method used is Descriptive Qualitative which determines the subjects of this study are several lecturers and students with data collection techniques prioritized from interviews and supported by observation and documentation. From the process in the field, it is found that the implementation of ELT which is materially integrated with Islamic Studies has been carried out even though it is still not in totality, and this provides insight to students so that they can communicate about Islamic Studies using English.